Self-lubricating wear-resistant anti-fog coating as well as preparation method and application thereof
By stacking the double-layer composite structure of an inorganic bonding layer and an organic anti-fog coating on the surface of the transparent optical material, the fog problem on the surface of the material when the temperature difference changes, and achieving high bonding strength, excellent anti-fog performance and good wear resistance.
Patent Information
- Application Number
- CN202510081642.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-01-20
AI Technical Summary
The surface of existing transparent optical materials is prone to mist when the temperature difference changes, resulting in a decrease in light transmittance and affecting visibility, and the mechanical strength and wear resistance of traditional anti-fog coatings are insufficient.
A double-layer composite structure of an inorganic bonding layer and an organic anti-fog coating arranged in sequence on the substrate surface is adopted. A combination of a vinyl silicon sol mixed coating and an anti-fog coating is formed to form a covalent bonded structure to improve the bonding strength and wear resistance of the coating.
It achieves high interface bonding strength and excellent anti-fog performance, while overcoming the problems of insufficient mechanical strength and wear resistance of traditional anti-fog coatings. The coating has good self-lubricating and wear resistance.
Smart Images

Figure CN119775811A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of material surface modification, and in particular to a self-lubricating, wear-resistant and anti-fog coating, and a preparation method and application thereof. Background Art
[0002] Transparent materials play an important role in aerospace, military equipment, medical equipment and optoelectronic devices due to their excellent optical properties. However, when the temperature difference changes in the environment, the water vapor in the air can easily condense into water droplets on the surface of the transparent material, generating fog, thereby affecting the light transmittance and visibility of the transparent material. For example, the fogging of the car windshield affects the driving vision, and the fogging of the endoscope during surgery is not conducive to the safe operation. At present, there are two main ideas to solve the problem of fogging on the surface of transparent optical materials: controlling the environmental parameters of the solid-liquid interface and surface modification. The former accelerates the evaporation of droplets by heating and increasing the air flow rate, such as the defogger and defrost system of the front windshield of the car. The method is costly and has limited applicable environment; the latter usually changes the wetting properties of the substrate by coating a hydrophilic coating. The coating absorbs water molecules through the hydrophilic group and reduces the surface tension of water, so that the contact angle of the water droplets on the substrate surface is reduced, and the droplets on the substrate surface can spread quickly to form a uniform layer of ink and no longer scatter the incident light, thereby achieving an anti-fog effect.
[0003] Coating a hydrophilic polymer onto a surface can effectively enhance the hydrophilicity of the interface and give the surface an excellent anti-fog effect. However, the hydrophilic polymer component has poor stability, the coating is prone to swelling and falling off in a humid environment, and is easily worn and loses transparency when subjected to external forces. Summary of the invention
[0004] In view of this, the purpose of the present invention is to provide a self-lubricating wear-resistant anti-fog coating and its preparation method and application. The self-lubricating wear-resistant anti-fog coating of the present invention has high interface bonding strength and excellent anti-fog performance, and its application substrate is not limited.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a self-lubricating, wear-resistant and anti-fog coating, comprising an inorganic bonding layer and an organic anti-fog coating sequentially stacked on the surface of a substrate;
[0007] The raw material for preparing the inorganic bonding layer is a vinyl silica sol mixed coating; the raw materials for preparing the vinyl silica sol mixed coating include tetraethyl orthosilicate, a vinyl silane coupling agent, a first alcohol, water and an inorganic acid;
[0008] The raw material for preparing the organic anti-fog coating is an anti-fog coating, and the raw materials for preparing the anti-fog coating include a hydrophilic polymer, monovinyl-terminated polydimethylsiloxane, a crosslinking agent, a photoinitiator and a second alcohol.
[0009] Preferably, the volume ratio of the first alcohol, tetraethyl orthosilicate, water and inorganic acid is (12-20): (1-5): (0.5-1.5): 0.2;
[0010] The mass ratio of tetraethyl orthosilicate to vinyl silane coupling agent is (20-150):1.
[0011] Preferably, the first alcohol comprises ethanol or isopropanol;
[0012] The inorganic acid includes nitric acid or hydrochloric acid;
[0013] The vinyl silane coupling agent includes one or more of methyl trivinyl silane, dimethyl divinyl silane, γ-methacryloxypropyl trimethoxy silane and vinyl tri (β-methoxyethoxy) silane.
[0014] Preferably, the method for preparing the vinyl silica sol mixed coating comprises the following steps:
[0015] Tetraethyl orthosilicate, a vinyl silane coupling agent, a first alcohol, water and an inorganic acid are mixed, and then hydrolyzed and aged in sequence to obtain the vinyl silica sol mixed coating.
[0016] The hydrophilic polymer includes one or more of polymethacrylic acid, polyvinyl pyrrolidone, polyethylene imine and polyethylene glycol;
[0017] The cross-linking agent includes one or more of polyethylene glycol diacrylate, pentaerythritol triacrylate, trimethylolpropane triacrylate and pentaerythritol hexaacrylate;
[0018] The photoinitiator includes one or more of benzophenone, 2-hydroxy-2-methyl-1-phenylpropanone and 1-hydroxycyclohexyl phenyl ketone;
[0019] The second alcohol includes ethanol or isopropanol.
[0020] Preferably, the mass ratio of the hydrophilic polymer, the monovinyl-terminated polydimethylsiloxane, the crosslinking agent, the photoinitiator and the second alcohol is (20-50): (1-10): (1-5): (0.1-0.5): (100-200).
[0021] Preferably, the method for preparing the anti-fog coating comprises the following steps:
[0022] The anti-fog coating is obtained by mixing a hydrophilic polymer, a monovinyl-terminated polydimethylsiloxane, a crosslinking agent, a photoinitiator and a second alcohol.
[0023] The present invention also provides a method for preparing the self-lubricating, wear-resistant and anti-fog coating described in the above technical solution, comprising the following steps:
[0024] After first coating the vinyl silica sol mixed coating on the surface of the substrate, curing is performed to obtain an inorganic adhesive layer;
[0025] After the anti-fog coating is secondly coated on the surface of the inorganic adhesive layer, UV curing is performed to obtain the self-lubricating, wear-resistant and anti-fog coating.
[0026] Preferably, the first coating method is dip coating, and the dip coating pulling speed is 10 to 200 mm / min;
[0027] The curing method is baking, the baking temperature is 60-150° C., and the time is 0.5-6 hours;
[0028] The second coating method is spin coating, which includes a first spin coating and a second spin coating performed sequentially; the first spin coating has a rotation speed of 200 to 500 rpm and a time of 5 s; the second spin coating has a rotation speed of 1500 to 3000 rpm and a time of 20 s.
[0029] The present invention also provides the use of the self-lubricating, wear-resistant and anti-fog coating described in the above technical solution or the self-lubricating, wear-resistant and anti-fog coating prepared by the preparation method described in the above technical solution in the field of anti-fogging on the surface of optical transparent parts.
[0030] The invention provides a self-lubricating, wear-resistant and anti-fog coating, comprising an inorganic bonding layer and an organic anti-fog coating which are sequentially stacked on the surface of a substrate; the raw material for preparing the inorganic bonding layer is a vinyl silica sol mixed coating; the raw materials for preparing the vinyl silica sol mixed coating include tetraethyl orthosilicate, a vinyl silane coupling agent, a first alcohol, water and an inorganic acid; the raw material for preparing the organic anti-fog coating is an anti-fog coating; the raw materials for preparing the anti-fog coating include a hydrophilic polymer, monovinyl-terminated polydimethylsiloxane, a crosslinking agent, a photoinitiator and a second alcohol. The self-lubricating, wear-resistant and anti-fog coating of the present invention is a double-layer composite structure, wherein the upper layer is an organic anti-fog coating and the lower layer is an inorganic bonding layer, the layers are connected by covalent bonds, and the bonding strength between the organic anti-fog coating and the substrate is improved; the organic anti-fog coating is a hydrophilic-hydrophobic interpenetrating network (hydrophilic polymer and hydrophobic polymer (monovinyl-terminated polydimethylsiloxane)), wherein the hydrophilic polymer network regulates the surface wettability and gives the coating anti-fog performance; the hydrophobic polymer has the functions of reducing interfacial friction interaction and improving anti-swelling ability, and chemically combines with the inorganic bonding bottom layer component to build adhesion strength and improve the wear resistance of the coating.
[0031] The present invention also provides a method for preparing the self-lubricating, wear-resistant and anti-fog coating of the above technical solution, comprising the following steps: first coating the vinyl silica sol mixed coating on the surface of the substrate, and then curing to obtain an inorganic bonding layer; second coating the anti-fog coating on the surface of the inorganic bonding layer, and then UV curing to obtain the self-lubricating, wear-resistant and anti-fog coating. In the present invention, the preparation method is simple and convenient, overcoming the problems of poor mechanical strength and weak wear resistance of traditional anti-fog coatings, and the coating can be modified on the surface of most materials, the production process is simple, and can meet the needs of practical applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 The transmittance curves of the cleaned glass sheet, the glass sheet modified with a pure hydrophilic polymer layer as described in Comparative Example 1, and the glass sheet modified with a self-lubricating, wear-resistant, and anti-fog coating as described in Example 1;
[0033] Figure 2 The anti-fog performance of the glass sheet modified with the self-lubricating wear-resistant anti-fog coating and the blank glass sheet prepared in Example 1 is shown in the figure;
[0034] Figure 3 The friction coefficient curves of the glass sheet modified with a pure hydrophilic polymer layer described in Comparative Example 1 and the glass sheet modified with a self-lubricating, wear-resistant and anti-fog coating described in Example 1;
[0035] Figure 4 It is a microscope picture of the glass sheet modified with a pure hydrophilic polymer layer described in Comparative Example 1 and the glass sheet modified with a self-lubricating, wear-resistant and anti-fog coating described in Example 1 after 50 friction tests.
[0036] Figure 5 Microscope images and anti-fog performance images of the glass sheets modified with the self-lubricating wear-resistant anti-fog coating prepared in Examples 2 to 5 after 50 friction tests. DETAILED DESCRIPTION
[0037] The present invention provides a self-lubricating, wear-resistant and anti-fog coating, comprising an inorganic bonding layer and an organic anti-fog coating sequentially stacked on the surface of a substrate;
[0038] The raw material for preparing the inorganic bonding layer is a vinyl silica sol mixed coating; the raw materials for preparing the vinyl silica sol mixed coating include tetraethyl orthosilicate, a vinyl silane coupling agent, a first alcohol, water and an inorganic acid;
[0039] The raw material for preparing the organic anti-fog coating is an anti-fog coating, and the raw materials for preparing the anti-fog coating include a hydrophilic polymer, monovinyl-terminated polydimethylsiloxane (PDMS-MA), a crosslinking agent, a photoinitiator and a second alcohol.
[0040] In the present invention, unless otherwise specified, all preparation raw materials are commercially available products well known to those skilled in the art.
[0041] The present invention has no special limitation on the material of the substrate, and any material well known to those skilled in the art can be used.
[0042] In the present invention, the thickness of the inorganic bonding layer is preferably 50 to 200 nm, more preferably 70 to 150 nm. In a specific embodiment of the present invention, the thickness of the inorganic bonding layer may be 70 nm, 100 nm, 150 nm, 80 nm or 120 nm.
[0043] In the present invention, the raw material for preparing the inorganic bonding layer is preferably a vinyl silica sol mixed coating; the raw materials for preparing the vinyl silica sol mixed coating preferably include tetraethyl orthosilicate, a vinyl silane coupling agent, a first alcohol, water and an inorganic acid.
[0044] In the present invention, the volume ratio of the first alcohol, tetraethyl orthosilicate, water and inorganic acid is preferably (12-20): (1-5): (0.5-1.5): 0.2, and more preferably (14-18): (2-3): (0.8-1.2): 0.2. In an embodiment of the present invention, the volume ratio of the first alcohol, tetraethyl orthosilicate, water and inorganic acid can be 12:2:1:0.2.
[0045] In the present invention, the mass ratio of tetraethyl orthosilicate to vinyl silane coupling agent is preferably (20-150):1, more preferably (60-120):1. In an embodiment of the present invention, the mass ratio of tetraethyl orthosilicate to vinyl silane coupling agent may be 40:1.
[0046] In the present invention, the first alcohol preferably includes ethanol or isopropanol. In an embodiment of the present invention, the first alcohol may be ethanol.
[0047] In the present invention, the mass percentage concentration of the inorganic acid is preferably 30-80%, more preferably 30-70%; the inorganic acid preferably includes nitric acid or hydrochloric acid, the mass percentage concentration of the nitric acid is preferably 68%, and the mass percentage concentration of the hydrochloric acid is preferably 36%. In an embodiment of the present invention, the inorganic acid can be nitric acid with a mass percentage concentration of 68%.
[0048] In the present invention, the vinyl silane coupling agent preferably includes one or more of methyl trivinyl silane, dimethyl divinyl silane (DDS), γ-methacryloxypropyl trimethoxy silane (KH570) and vinyl tri (β-methoxyethoxy) silane (A-172). When the vinyl silane coupling agent is two or more of the above specific selections, the present invention has no special restrictions on the ratio of the above specific substances, and they can be mixed in any ratio. In an embodiment of the present invention, the vinyl silane coupling agent can be DDS, KH570 or A-172.
[0049] In the present invention, the preparation method of the vinyl silica sol mixed coating comprises the following steps:
[0050] Tetraethyl orthosilicate, a vinyl silane coupling agent, a first alcohol, water and an inorganic acid are mixed, and then hydrolyzed and aged in sequence to obtain the vinyl silica sol mixed coating.
[0051] In the present invention, the mixing is preferably carried out under stirring conditions. The present invention does not have any special limitation on the stirring process, and the stirring process can be carried out by a process well known to those skilled in the art. In an embodiment of the present invention, the mixing can be carried out by uniformly mixing the first alcohol, tetraethyl orthosilicate, water and inorganic acid under stirring conditions, and then adding the vinyl silane coupling agent.
[0052] In the present invention, the hydrolysis temperature is preferably 20 to 30°C, more preferably 23 to 27°C, and the time is preferably 1 to 6 hours, more preferably 1 to 3 hours. In the present invention, the hydrolysis is preferably carried out under stirring. The present invention does not have any special restrictions on the stirring process, and the process well known to those skilled in the art can be used. In an embodiment of the present invention, the hydrolysis temperature can be 25°C and the time can be 1 hour.
[0053] In the present invention, the temperature of the static aging is preferably 20-30°C, the time is preferably 1-7 days, more preferably 3-5 days. In an embodiment of the present invention, the temperature of the static aging can be 25°C, and the time can be 3 days or 5 days.
[0054] In the present invention, the thickness of the organic anti-fog coating is preferably 50 to 150 μm, more preferably 100 μm.
[0055] In the present invention, the hydrophilic polymer preferably includes one or more of polymethacrylic acid (PAA), polyvinyl pyrrolidone (PVP), polyethyleneimine (PEI) and polyethylene glycol (PEG). When the hydrophilic polymer is two or more of the above specific selections, the present invention does not have any special restrictions on the ratio of the above specific substances, and can be mixed in any ratio. In an embodiment of the present invention, the hydrophilic polymer can be PVP, PEG, PEI, or PEI and PVP in a mass ratio of 2:3.
[0056] In the present invention, the crosslinking agent includes one or more of polyethylene glycol diacrylate, pentaerythritol triacrylate, trimethylolpropane triacrylate and pentaerythritol hexaacrylate. When the crosslinking agent is two or more of the above specific selections, the present invention has no special restrictions on the ratio of the above specific substances, and they can be mixed in any ratio. In an embodiment of the present invention, the crosslinking agent can be pentaerythritol triacrylate.
[0057] In the present invention, the photoinitiator preferably includes one or more of benzophenone (Bp), 2-hydroxy-2-methyl-1-phenylpropanone and 1-hydroxycyclohexyl phenyl ketone (UV-184). When the photoinitiator is two or more of the above specific selections, the present invention has no special restrictions on the ratio of the above specific substances, and they can be mixed in any ratio. In an embodiment of the present invention, the photoinitiator can be UV-184 or Bp.
[0058] In the present invention, the second alcohol preferably includes ethanol or isopropanol. In an embodiment of the present invention, the second alcohol may be ethanol.
[0059] In the present invention, the mass ratio of the hydrophilic polymer, the monovinyl-terminated polydimethylsiloxane, the crosslinking agent, the photoinitiator and the second alcohol is preferably (20-50): (1-10): (1-5): (0.1-0.5): (100-200), more preferably (30-40): (3-7): (3-5): (0.2-0.3): (150-200). In an embodiment of the present invention, the mass ratio of the hydrophilic polymer, the monovinyl-terminated polydimethylsiloxane, the crosslinking agent, the photoinitiator and the second alcohol can be 30:7:3:0.2:150, 40:3:4:0.2:180, 40:4:4:0.2:200, 30:3:3:0.2:200 or 50:5:5:0.3:200.
[0060] In the present invention, the preparation method of the anti-fog coating preferably comprises the following steps:
[0061] The anti-fog coating is obtained by mixing a hydrophilic polymer, a monovinyl-terminated polydimethylsiloxane, a crosslinking agent, a photoinitiator and a second alcohol.
[0062] In the present invention, the mixing is preferably carried out at room temperature, in the dark and under stirring conditions, and the stirring time is preferably 6 to 24 hours, more preferably 12 hours. The present invention does not have any special limitation on the stirring speed, and the stirring speed is carried out at a speed familiar to those skilled in the art, and uniform mixing is ensured within the above stirring time.
[0063] The present invention also provides a method for preparing the self-lubricating, wear-resistant and anti-fog coating described in the above technical solution, comprising the following steps:
[0064] After first coating the vinyl silica sol mixed coating on the surface of the substrate, curing is performed to obtain an inorganic adhesive layer;
[0065] After the anti-fog coating is secondly coated on the surface of the inorganic adhesive layer, UV curing is performed to obtain the self-lubricating, wear-resistant and anti-fog coating.
[0066] In the present invention, the vinyl silica sol mixed coating is first coated on the surface of the substrate and then cured to obtain an inorganic bonding layer.
[0067] In the present invention, the first coating method is preferably dip coating, and the pulling speed of the dip coating is preferably 10 to 200 mm / min, more preferably 20 to 100 mm / min. In an embodiment of the present invention, the pulling speed of the dip coating can be 20 mm / min, 50 mm / min, 100 mm / min, 30 mm / min or 60 mm / min.
[0068] In the present invention, the curing method is preferably baking; the baking temperature is preferably 60 to 150°C, more preferably 80 to 120°C; the baking time is preferably 0.5 to 6 hours, more preferably 0.5 to 2 hours. In an embodiment of the present invention, the baking temperature can be 80°C or 120°C, and the baking time can be 1 hour or 0.5 hours.
[0069] After obtaining the inorganic adhesive layer, the present invention applies the anti-fog coating on the surface of the inorganic adhesive layer for the second time, and then performs UV curing to obtain the self-lubricating, wear-resistant and anti-fog coating.
[0070] In the present invention, the second coating method is preferably spin coating, and the spin coating preferably includes a first spin coating and a second spin coating performed sequentially, the first spin coating preferably has a rotation speed of 200 to 500 rpm, more preferably 300 to 400 rpm, and the time is preferably 5 s; the second spin coating preferably has a rotation speed of 1500 to 3000 rpm, more preferably 2000 to 2500 rpm, and the time is preferably 20 s. In an embodiment of the present invention, the first spin coating may have a rotation speed of 300 rpm, and the time may be 5 s; the second spin coating may have a rotation speed of 2000 rpm, and the time may be 20 s.
[0071] In the present invention, the temperature of the UV curing is preferably room temperature, the wavelength of the UV curing light is preferably 365 nm, and the light intensity is preferably 180 to 250 mW / cm 2 , more preferably 190 to 200 mW / cm 2 The time is preferably 0.5 to 3 hours, more preferably 1 to 2 hours. In an embodiment of the present invention, the UV curing light wavelength can be 365nm, and the light intensity can be 250mW / cm 2 , the time can be 2h.
[0072] The present invention also provides the use of the self-lubricating, wear-resistant and anti-fog coating described in the above technical solution or the self-lubricating, wear-resistant and anti-fog coating prepared by the preparation method described in the above technical solution in the field of anti-fogging on the surface of optical transparent parts. The present invention does not have any special limitation on the method of the application, and the method well known to those skilled in the art can be used.
[0073] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0074] Example 1
[0075] 12 mL of ethanol, 2 mL of tetraethyl orthosilicate, 1 mL of water and 0.2 mL of nitric acid with a mass percentage concentration of 68% were mixed uniformly under stirring, and then 0.05 mL of KH570 was added, and the mixture was stirred for 1 hour and aged for 3 days to obtain a vinyl silica sol mixed coating;
[0076] 30 g of PVP, 7 g of PDMS-MA, 3 g of pentaerythritol triacrylate, 0.2 g of UV-184 and 150 g of ethanol were mixed and stirred in the dark until a transparent and uniform solution was obtained to obtain an anti-fog coating;
[0077] The cleaned glass sheet was immersed in the vinyl silica sol mixed coating, then pulled out with a pulling machine at a speed of 20 mm / min, and baked at 80° C. for 1 h to obtain an inorganic bonding layer (thickness of 70 nm);
[0078] The anti-fog coating was spin-coated on the surface of the inorganic adhesive layer (first at a speed of 300 rpm for 5 seconds, then at a speed of 2000 rpm for 20 seconds), and then cured under 365 nm UV light for 2 hours (light intensity of 250 mW / cm 2 ) to prepare a glass sheet modified with a self-lubricating, wear-resistant and anti-fog coating (the thickness of the organic anti-fog coating is 100 μm).
[0079] Comparative Example 1
[0080] 30 g of PVP, 3 g of pentaerythritol triacrylate, 0.2 g of UV-184 and 150 g of ethanol were mixed and stirred in the dark until a transparent and uniform solution was obtained to obtain a comparative antifog coating;
[0081] The anti-fog coating was spin-coated on the cleaned glass surface (first at 300 rpm for 5 s, then at 2000 rpm for 20 s), and then cured under 365 nm UV light for 2 h (light intensity of 250 mW / cm 2 ) to prepare a glass sheet modified with a pure hydrophilic polymer layer.
[0082] Test Example 1
[0083] The transmittance of the cleaned glass sheet, the glass sheet modified with a pure hydrophilic polymer layer as described in Comparative Example 1, and the glass sheet modified with a self-lubricating, wear-resistant, and anti-fog coating as described in Example 1 were tested by a UV-visible spectrophotometer. The test results are as follows: Figure 1 As shown by Figure 1 It can be seen that the transmittance curves of the cleaned glass sheet, the glass sheet modified with a pure hydrophilic polymer layer described in Comparative Example 1, and the glass sheet modified with a self-lubricating, wear-resistant, and anti-fog coating described in Example 1 are similar, indicating that the coating has little effect on the light transmission performance of the glass;
[0084] The glass sheet modified with the self-lubricating wear-resistant anti-fog coating prepared in Example 1 was placed on a 60°C water bath, about 10 cm away from the liquid surface, and left to stand for different periods of time. A blank glass sheet was used as a control sample. The anti-fog performance of the surface was as follows: Figure 2 As shown by Figure 2 It can be seen that after 12 hours of anti-fog test, there are still no obvious fog droplets on the surface of the wear-resistant anti-fog coating, which shows that the coating has excellent anti-fog performance;
[0085] The glass sheet modified with a pure hydrophilic polymer layer described in Comparative Example 1 and the glass sheet modified with a self-lubricating wear-resistant anti-fog coating described in Example 1 were respectively placed under a load of 2N and a frequency of 1Hz and rubbed against flannel in air, wherein: Figure 3 The friction coefficient curves of the glass sheet modified with a pure hydrophilic polymer layer described in Comparative Example 1 and the glass sheet modified with a self-lubricating, wear-resistant and anti-fog coating described in Example 1 are shown in FIG. Figure 3 It can be seen that compared with the high friction coefficient (0.25) of the glass sheet modified with the pure water polymer layer described in Comparative Example 1, the friction coefficient of the coating surface of Example 1 can still be maintained at about 0.05 within 10,000 cycles, and has good self-lubricating and wear-resistant properties;
[0086] The glass sheet modified with the pure hydrophilic polymer layer described in Comparative Example 1 and the glass sheet modified with the self-lubricating wear-resistant anti-fog coating described in Example 1 were subjected to 50 friction tests and then placed under an optical microscope to observe the surface morphology. Figure 4 The microscopic images of the glass sheet modified with the pure hydrophilic polymer layer described in Comparative Example 1 and the glass sheet modified with the self-lubricating wear-resistant anti-fog coating described in Example 1 after 50 friction tests are shown in FIG. Figure 4 It can be seen that obvious and numerous wear marks appear on the surface of the pure hydrophilic polymer layer in the glass sheet modified with the pure hydrophilic polymer layer described in Comparative Example 1; in comparison, no obvious wear marks are observed on the surface of the self-lubricating, wear-resistant, anti-fog coating in the glass sheet modified with the self-lubricating, wear-resistant, anti-fog coating described in Example 1, indicating that the self-lubricating, wear-resistant, anti-fog coating has good wear resistance.
[0087] Example 2
[0088] 12 mL of ethanol, 2 mL of tetraethyl orthosilicate, 1 mL of water and 0.2 mL of 68% nitric acid were mixed evenly under stirring, and then 0.05 mL of DDS was added, and the mixture was stirred for 1 h and aged for 5 days to obtain a vinyl silica sol mixed coating.
[0089] 40 g of PVP, 3 g of PDMS-MA, 4 g of pentaerythritol triacrylate, 0.2 g of UV-184 and 180 g of ethanol were mixed and stirred in the dark until a transparent and uniform solution was obtained to obtain an anti-fog coating;
[0090] The cleaned glass sheet was immersed in the vinyl silica sol mixed coating, then pulled out with a pulling machine at a speed of 50 mm / min, and baked at 120° C. for 0.5 h to obtain an inorganic bonding layer (thickness of 100 nm);
[0091] The anti-fog coating was spin-coated on the surface of the inorganic adhesive layer (first at a speed of 300 rpm for 5 seconds, then at a speed of 2000 rpm for 20 seconds), and then cured under 365 nm UV light for 2 hours (light intensity of 250 mW / cm 2 ) to prepare a glass sheet modified with a self-lubricating, wear-resistant and anti-fog coating (the thickness of the organic anti-fog coating is about 98 μm).
[0092] After testing, the anti-fog performance, lubrication performance and wear resistance of the glass sheet modified with the self-lubricating wear-resistant anti-fog coating are similar to those of Example 1. After 50 friction tests, only slight scratches appeared on the coating surface, and the anti-fog performance of the coating was good ( Figure 5 ).
[0093] Example 3
[0094] 12 mL of ethanol, 2 mL of tetraethyl orthosilicate, 1 mL of water and 0.2 mL of 68% nitric acid were mixed evenly under stirring, and then 0.05 mL of A-172 was added, and the mixture was stirred for 1 h and allowed to stand for 3 days to obtain a vinyl silica sol mixed coating.
[0095] 40 g of PEG, 4 g of PDMS-MA, 4 g of pentaerythritol triacrylate, 0.2 g of UV-184 and 200 g of ethanol were mixed and stirred in the dark until a transparent and uniform solution was obtained to obtain an anti-fog coating;
[0096] The cleaned glass sheet is immersed in the vinyl silica sol mixed coating, then pulled out with a pulling machine at a speed of 100 mm / min, and baked at 120° C. for 0.5 h to obtain an inorganic bonding layer (thickness of 150 nm);
[0097] The anti-fog coating was spin-coated on the surface of the inorganic adhesive layer (first at a speed of 300 rpm for 5 seconds, then at a speed of 2000 rpm for 20 seconds), and then cured under 365 nm UV light for 2 hours (light intensity of 250 mW / cm 2 ) to prepare a glass sheet modified with a self-lubricating, wear-resistant and anti-fog coating (the thickness of the organic anti-fog coating is about 95 μm).
[0098] After testing, the anti-fog performance, lubrication performance and wear resistance of the glass sheet modified with the self-lubricating wear-resistant anti-fog coating are similar to those of Example 1. After 50 friction tests, only slight scratches appeared on the coating surface, and the anti-fog performance of the coating was good ( Figure 5 ).
[0099] Example 4
[0100] 12 mL of ethanol, 2 mL of tetraethyl orthosilicate, 1 mL of water and 0.2 mL of 68% nitric acid were mixed evenly under stirring, and then 0.05 mL of KH570 was added, and the mixture was stirred for 1 h and aged for 5 days to obtain a vinyl silica sol mixed coating.
[0101] 30 g PEI, 3 g PDMS-MA, 3 g pentaerythritol triacrylate, 0.2 g Bp and 200 g ethanol were mixed and stirred in the dark until a transparent and uniform solution was obtained to obtain an anti-fog coating;
[0102] The cleaned glass sheet is immersed in the vinyl silica sol mixed coating, then pulled out with a pulling machine at a speed of 30 mm / min, and baked at 80° C. for 0.5 h to obtain an inorganic bonding layer (with a thickness of 80 nm);
[0103] The anti-fog coating was spin-coated on the surface of the inorganic adhesive layer (first at a speed of 300 rpm for 5 seconds, then at a speed of 2000 rpm for 20 seconds), and then cured under 365 nm UV light for 2 hours (light intensity of 250 mW / cm 2 ) to prepare a glass sheet modified with a self-lubricating, wear-resistant and anti-fog coating (the thickness of the organic anti-fog coating is about 90 μm).
[0104] After testing, the anti-fog performance, lubrication performance and wear resistance of the glass sheet modified with the self-lubricating wear-resistant anti-fog coating are similar to those of Example 1. After 50 friction tests, only shallow scratches appeared on the coating surface, and the anti-fog performance of the coating was good ( Figure 5 ).
[0105] Example 5
[0106] 12 mL of ethanol, 2 mL of tetraethyl orthosilicate, 1 mL of water and 0.2 mL of 68% nitric acid were mixed evenly under stirring, and then 0.03 mL of KH570 and 0.02 mL of A-172 were added, and the mixture was stirred for 1 h and aged for 5 days to obtain a vinyl silica sol mixed coating.
[0107] 20 g PEI, 30 g PVP, 5 g PDMS-MA, 5 g pentaerythritol triacrylate, 0.3 g Bp and 200 g ethanol were mixed and stirred in the dark until a transparent and uniform solution was obtained to obtain an anti-fog coating;
[0108] The cleaned glass sheet is immersed in the vinyl silica sol mixed coating, then pulled out with a pulling machine at a speed of 60 mm / min, and baked at 80° C. for 1 h to obtain an inorganic bonding layer (thickness of 120 nm);
[0109] The anti-fog coating was spin-coated on the surface of the inorganic adhesive layer (first at a speed of 300 rpm for 5 seconds, then at a speed of 2000 rpm for 20 seconds), and then cured under 365 nm UV light for 2 hours (light intensity of 250 mW / cm 2 ) to prepare a glass sheet modified with a self-lubricating, wear-resistant and anti-fog coating (the thickness of the organic anti-fog coating is about 108 μm).
[0110] After testing, the anti-fog performance, lubrication performance and wear resistance of the glass sheet modified with the self-lubricating wear-resistant anti-fog coating are similar to those of Example 1. After 50 friction tests, only slight scratches appeared on the coating surface, and the anti-fog performance of the coating was good ( Figure 5 ).
[0111] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. A self-lubricating, wear-resistant and anti-fog coating, characterized in that: It includes an inorganic adhesive layer and an organic anti-fog coating layer sequentially stacked on the surface of a substrate; The raw material for preparing the inorganic bonding layer is a vinyl silica sol mixed coating; the raw materials for preparing the vinyl silica sol mixed coating include tetraethyl orthosilicate, a vinyl silane coupling agent, a first alcohol, water and an inorganic acid; The raw material for preparing the organic anti-fog coating is an anti-fog coating; the raw materials for preparing the anti-fog coating include a hydrophilic polymer, monovinyl-terminated polydimethylsiloxane, a crosslinking agent, a photoinitiator and a second alcohol.
2. The self-lubricating, wear-resistant and anti-fog coating according to claim 1, characterized in that: The volume ratio of the first alcohol, tetraethyl orthosilicate, water and inorganic acid is (12-20): (1-5): (0.5-1.5): 0.2; The mass ratio of tetraethyl orthosilicate to vinyl silane coupling agent is (20-150):
1.
3. The self-lubricating, wear-resistant and anti-fog coating according to claim 1 or 2, characterized in that: The first alcohol includes ethanol or isopropanol; The inorganic acid includes nitric acid or hydrochloric acid; The vinyl silane coupling agent includes one or more of methyl trivinyl silane, dimethyl divinyl silane, γ-methacryloxypropyl trimethoxy silane and vinyl tri (β-methoxyethoxy) silane.
4. The self-lubricating, wear-resistant and anti-fog coating according to claim 3, characterized in that: The preparation method of the vinyl silica sol mixed coating comprises the following steps: Tetraethyl orthosilicate, a vinyl silane coupling agent, a first alcohol, water and an inorganic acid are mixed, and then hydrolyzed and aged in sequence to obtain the vinyl silica sol mixed coating.
5. The self-lubricating, wear-resistant and anti-fog coating according to claim 1, characterized in that: The hydrophilic polymer includes one or more of polymethacrylic acid, polyvinyl pyrrolidone, polyethylene imine and polyethylene glycol; The cross-linking agent includes one or more of polyethylene glycol diacrylate, pentaerythritol triacrylate, trimethylolpropane triacrylate and pentaerythritol hexaacrylate; The photoinitiator includes one or more of benzophenone, 2-hydroxy-2-methyl-1-phenylpropanone and 1-hydroxycyclohexyl phenyl ketone; The second alcohol includes ethanol or isopropanol.
6. The self-lubricating, wear-resistant and anti-fog coating according to claim 1 or 5, characterized in that: The mass ratio of the hydrophilic polymer, the monovinyl-terminated polydimethylsiloxane, the crosslinking agent, the photoinitiator and the second alcohol is (20-50): (1-10): (1-5): (0.1-0.5): (100-200).
7. The self-lubricating, wear-resistant and anti-fog coating according to claim 6, characterized in that: The preparation method of the anti-fog coating comprises the following steps: The anti-fog coating is obtained by mixing a hydrophilic polymer, a monovinyl-terminated polydimethylsiloxane, a crosslinking agent, a photoinitiator and a second alcohol.
8. The method for preparing the self-lubricating, wear-resistant and anti-fog coating according to any one of claims 1 to 7, characterized in that: The following steps are involved: After first coating the vinyl silica sol mixed coating on the surface of the substrate, curing is performed to obtain an inorganic adhesive layer; After the anti-fog coating is secondly coated on the surface of the inorganic adhesive layer, UV curing is performed to obtain the self-lubricating, wear-resistant and anti-fog coating.
9. The preparation method according to claim 8, characterized in that: The first coating method is dip coating, and the dip coating pulling speed is 10 to 200 mm / min; The curing method is baking, the baking temperature is 60-150° C., and the time is 0.5-6 hours; The second coating method is spin coating, which includes a first spin coating and a second spin coating performed sequentially; the first spin coating has a rotation speed of 200 to 500 rpm and a time of 5 s; the second spin coating has a rotation speed of 1500 to 3000 rpm and a time of 20 s.
10. Use of the self-lubricating, wear-resistant and anti-fog coating according to any one of claims 1 to 7 or the self-lubricating, wear-resistant and anti-fog coating prepared by the preparation method according to claim 8 or 9 in the field of anti-fogging on the surface of optical transparent parts.
Citation Information
Patent Citations
Ultraviolet light curing anti fogging coating composite and preparing method thereof
CN101602913A
Ultraviolet curing coating and preparation method thereof, and super-hydrophilic transparent antifogging coating layer and preparation method thereof
CN105176371A
Preparation method of hydrophilic antifogging coating layer for surface of transparent base material
CN108659244A
Transparent super-hydrophilic coating as well as preparation method and application thereof
CN114773939A
Mixed polymer brush coating layer resistant to wear in dry / wet environment and preparation method of mixed polymer brush coating layer
CN117861976A